Widzenie awangardy, red. Agata Stankowska, Marcin Telicki i Agata Lewandowska, „Literatura i Sztuka”, tom 5, Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, Poznań 2018 - Karpowicz, Agnieszka (Zagadnienia Rodzajów Literackich, 2019)
-